2021
DOI: 10.1063/5.0040515
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of azimuthal B-fields in Z-pinch plasmas using Z-pinch-driven ion deflectometry

Abstract: B-field measurements are crucial for the study of high-temperature and high-energy-density plasmas. A successful diagnostic method, ion deflectometry (radiography), is commonly employed to measure MGauss magnetic fields in laser-produced plasmas. It is based on the detection of multi-MeV ions, which are deflected in B-fields and measure their path integral. Until now, protons accelerated via laser–target interactions from a point-like source have been utilized for the study of Z-pinch plasmas. In this paper, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Our analysis [23] of the general principles of ion deflectometry in z-pinch B-fields and later the experimental measurements [9] have demonstrated that the ion beams fired axially into the z-pinch can investigate the specific distribution of the B-fields inside the z-pinch. To map the magnetic fields along the z-pinch axis, the electrodes must be permeable for passing ions from the ion source and to the ion detector.…”
Section: Basics Of Ion Deflectometry In the Z-pinch Geometrymentioning
confidence: 84%
See 1 more Smart Citation
“…Our analysis [23] of the general principles of ion deflectometry in z-pinch B-fields and later the experimental measurements [9] have demonstrated that the ion beams fired axially into the z-pinch can investigate the specific distribution of the B-fields inside the z-pinch. To map the magnetic fields along the z-pinch axis, the electrodes must be permeable for passing ions from the ion source and to the ion detector.…”
Section: Basics Of Ion Deflectometry In the Z-pinch Geometrymentioning
confidence: 84%
“…The first self-sustained deflectometry measurements of the z-pinch B-fields not requiring intense laser pulses were performed in 2019 on 3 MA deuterium hybrid gas-puff z-pinch driven by the GIT-12 generator [9]. In these experiments, a rapid current disruption of the plasma neck in the z-pinch generated strong transient electric fields that accelerated hydrogen ion beams up to energies of tens of MeV [10].…”
Section: Introductionmentioning
confidence: 99%